2016
DOI: 10.1182/blood.v128.22.3794.3794
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing in Venous Thromboembolic Disease Identifies Excess Mutation Burden in PROS1, PROC, SERPINC1 and STAB2

Abstract: Deep vein thrombosis and pulmonary embolism, collectively referred to as venous thromboembolism (VTE), are the third leading cause of cardiovascular death in the United States. Genetic factors account for 50-60% of VTE risk and a recent meta-analysis of genome-wide association studies confirmed that common variants in F5, ABO, and seven other loci are associated with VTE. Rare mutations in the anticoagulant genes PROC, PROS1 and SERPINC1 have been linked to VTE in family studies. In order to identify new genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Pathogenic variants in STAB2 have been found to be associated with large elevations in plasma VWF:Ag levels (> 33%) in both association and exome sequencing studies , and modify the ability of stabilin‐2‐expressing cells to bind and internalize VWF in vitro . Pathogenic STAB2 variants have also been shown to be associated with the incidence of VTE ; however, given the scavenger function of stabilin‐2, altered clearance of non‐VWF plasma coagulation factors or inflammatory regulators may also contribute to the pathogenic basis of this observation.…”
Section: Genes Influencing Vwf Clearancementioning
confidence: 99%
“…Pathogenic variants in STAB2 have been found to be associated with large elevations in plasma VWF:Ag levels (> 33%) in both association and exome sequencing studies , and modify the ability of stabilin‐2‐expressing cells to bind and internalize VWF in vitro . Pathogenic STAB2 variants have also been shown to be associated with the incidence of VTE ; however, given the scavenger function of stabilin‐2, altered clearance of non‐VWF plasma coagulation factors or inflammatory regulators may also contribute to the pathogenic basis of this observation.…”
Section: Genes Influencing Vwf Clearancementioning
confidence: 99%
“…Several other polymorphisms/genes have been proposed as risk factors for VTE but these lack compelling evidence, including robust statistical replication in independent studies, to be definitively claimed as susceptibility variants/genes for the disease. These include the rs2232710 of SERPINA10 , which encodes the Protein Z‐Dependent Protease Inhibitor of coagulation factors Xa and XIa (Folsom et al , ; Gorski et al , ); SERPINE1 rs2227631, influencing circulating plasminogen activator inhibitor‐1 (PAI‐1) levels (Huang et al , ); C4BPB/C4BPA rs3813948, affecting PS associated phenotypes (Buil et al , ); the rs7080536 of the HABP2 gene, encoding factor VII (FVII) activating protease (Ahmad‐Nejad et al , ); HIVEP1 rs169713 with, as yet, no associated intermediate phenotype (Morange et al , ); F13A1 rs5985 (Val34Leu) (Wells et al , ), influencing FXIII activity (Kohler et al , ; Wartiovaara et al , ); APOH rs8178847, associated with thrombin generation (Tang et al , ); genetic variations at the STAB 2 , STX2 and TC2N loci with suggestive impact on VTE risk (Germain et al , ; Morange et al , ; Smith et al , ; Desch et al , ) via their influence on VWF levels (Smith et al , ); and the rs4602861 (Germain et al , ; Klarin et al , ) at the ZFPM2 locus, whose suspected association with VTE could involve platelet count (Gieger et al , ) and vascular endothelial growth factor (Debette et al , ). Some of these associations, if true, could be restricted to some specific ethnic populations.…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%
“…Although the associations between VWF and the receptors SR‐A1, asialoglycoprotein receptor, and LRP‐1 were characterized in candidate gene rationalized studies, the influence of stabilin‐2 on VWF clearance was first suggested by the Cohorts for Heart and Aging Research in Genome Epidemiology (CHARGE) genome‐wide association study (GWAS) meta‐analysis, which associated common variants with plasma levels of VWF or its binding partner the coagulation cofactor factor VIII (FVIII) . In follow‐up studies, rare and common STAB2 gene variants have been associated with VWF plasma levels in normal individuals and patients with type 1 VWD or low VWF, or an increased risk for venous thromboembolism . In addition to the STAB2 locus, the CHARGE GWAS identified variants in the genes encoding two other cell surface receptors, the endocytic lectin receptor CLEC4M and the scavenger receptor SCARA5 (Scavenger Receptor Class A Member 5, or SR‐A5), as being associated with plasma VWF and/or FVIII …”
Section: Introductionmentioning
confidence: 99%